Evaluation and analysis of respiratory infectious disease prevention behaviors in older adults - Yu, Liliang; Liu, Min; Tan, Qing; Wang, Dan; Chen, Xiaoyun; Zhao, Mingming; Long, Jiang; Fan, Mingyue; Zheng, Daikun (Frontiers in Public Health, 2024)
BackgroundRespiratory infectious diseases (RIDs) are a global public health problem, characterized by strong infectivity, high transmissibility, and a high incidence in the population. This study aimed to explore RID prevention behaviors among older adults and analyze their influencing factors.MethodsA cross-sectional study was conducted to examine RID prevention behaviors among 2219 Chinese older adults. Analysis of variance and the Kruskal–Wallis test were used to compare behaviors among subjects with different characteristics. Pearson's correlation analysis was used to assess the relationships between knowledge, skills, and behavior, and a generalized linear model was used for multi-factor analysis.ResultsThe participants in this questionnaire survey were predominantly older adults individuals aged 65–70 years (45.65%), with no more than a primary school educational level (86.70%). Univariate analysis revealed statistically significant associations between age, education, place of residence, living condition, marital status, annual income in the past year, type of medical insurance, health status, smoking status, drinking status, weekly exercise durations, and sleep status in older adults and their RID prevention behavior. Pearson's correlation analysis indicated a moderate correlation between knowledge, skills, and behavioral scores. Multivariate analysis identified place of residence, annual income, smoking habits, alcohol consumption, exercise frequency, knowledge level, and skill level as influential factors for behaviors related to the prevention and control of RID in older adults.ConclusionOur results confirm the importance of a healthy lifestyle in RID prevention among older adults, especially in terms of smoking, alcohol consumption, and regular exercise, and provide empirical evidence for the development of health promotion programs for older adults people, particularly in rural areas.